Transformasi Limbah Organik Rumah Tangga menjadi Pewarna Alami pada Kain Tie Dye sebagai Media Ekspresi Imajinatif dan Kreativitas Berkelanjutan - Faikotus Silvi; Ahwalia Annajah; M Reza Hafid Al Faris; Farah Salsabila Hakim; Firman Hidayat; Nabila Indah Cahyani; Arik Aguk Wardoyo; Rizki Putri Wardani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
The problem of household organic waste remains an environmental issue frequently encountered in the community, especially since most waste is simply disposed of without being reused. On the other hand, the use of synthetic dyes in textile activities also has the potential to cause environmental pollution due to the chemical content that is difficult to decompose. This community service activity aims to increase the creativity and environmental awareness of elementary school students through the use of household organic waste as a natural dye in tie dye fabrics. The activity was carried out at SDN Tanggulangin 1, Bondowoso Regency, involving 23 fifth-grade elementary school students. Based on the results of initial observations, SDN Tanggulangin 1 students had never received learning about the use of organic waste as a natural dye so that household waste was still seen as waste that had no use value. The method used was participatory-based direct practice through stages of socialization, demonstration, tie dye making practice, evaluation, and mentoring. The natural materials used included turmeric, butterfly pea flowers, and dragon fruit peel as sources of natural dyes. The results of the activity showed that students were very enthusiastic about participating in the entire series of activities. The average pre-test score of 41.30 increased to 83.48 in the post-test with an increase of 42.18% and an N-Gain score of 0.69 which is included in the medium to high category. In addition to improving students' understanding of organic waste management, this activity is also able to foster creativity, artistic skills, critical thinking skills, and environmental awareness. Thus, the use of organic waste as a natural tie dye can be an alternative for creative and environmentally friendly learning in elementary schools. This program is designed to be continued by teachers through art learning activities and the Pancasila Student Profile Strengthening Project (P5) with the theme of a sustainable lifestyle